Benefits of a calcium antagonist, nifedipine GITS, in arterial hypertension treatment - V. B. Mychka; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2008)
Based on the results of international clinical trials, the clinical benefits of a dihydropyridine calcium antagonist, nifedipine GITS (slow-release gastrointestinal therapeutic-system) are discussed. Nifedipine GITS has been demonstrated to reduce cardiovascular morbidity and mortality effectively. The medication is safe and metabolically neutral even when administered as a long-term treatment.